2005
DOI: 10.1385/abab:121:1-3:0105
|View full text |Cite
|
Sign up to set email alerts
|

Lipase Production by Solid-State Fermentation: Cultivation Conditions and Operation of Tray and Packed-Bed Bioreactors

Abstract: The production of lipase by Penicillium simplicissimum in solid-state fermentation was studied using babassu cake as the basal medium. Tray-type and packed-bed bioreactors were employed. In the former, the influence of temperature; content of the medium, and medium supplementation with olive oil, sugarcane molasses, corn steep liquor, and yeast hydrolysate was studied. For all combinations of supplements, a temperature of 30 degrees C, a moisture content of 70%, and a concentration of carbon source of 6.25% (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 16 publications
3
30
1
4
Order By: Relevance
“…Production of lipase by Penicillium simplicissium in SSF, using babassu cake as the basal medium, was investigated in the presence of olive oil, sugarcane molasses, corn steep liquor and yeast extract. Olive oil and corn steep liquor were found the most suited carbon and nitrogen sources for lipase synthesis [78]. Rigo et al [79] reported that the medium supplementations with urea and soybean oil significantly increased lipase production by Penicillium sp.…”
Section: Regulation Of Lipase Production Concerning the Medium Composmentioning
confidence: 99%
“…Production of lipase by Penicillium simplicissium in SSF, using babassu cake as the basal medium, was investigated in the presence of olive oil, sugarcane molasses, corn steep liquor and yeast extract. Olive oil and corn steep liquor were found the most suited carbon and nitrogen sources for lipase synthesis [78]. Rigo et al [79] reported that the medium supplementations with urea and soybean oil significantly increased lipase production by Penicillium sp.…”
Section: Regulation Of Lipase Production Concerning the Medium Composmentioning
confidence: 99%
“…Este resíduo, denominado torta de babaçu, foi utilizado como meio de cultivo basal para a fermentação, que foi conduzida por 72 horas com a torta de babaçu moída e peneirada (diâmetro médio de 0,315 mm). O teor de umidade foi mantido em 70% e a temperatura em 30 °C (GUTARRA et al, 2005(GUTARRA et al, , 2007. Após a fermentação, parte da torta fermentada foi extraída e utilizada para determinação da atividade lipásica, segundo metodologia descrita em Gutarra et al, (2007).…”
Section: Fermentação Em Meio Sólido (Fms)unclassified
“…A atividade lipásica do extrato bruto foi determinada por método espectrofotométrico, utilizando-se p-nitrofenillaureato como substrato, conforme descrito por Gutarra et al (2005). Uma unidade de atividade lipásica é definida como a quantidade de enzima que libera 1 µmol de p-nitrofenol por minuto, nas condições de reação.…”
Section: Métodos Analíticosunclassified
“…Through this analysis it is evident that extremes in temperature and moisture tend to decrease lipase production, since low temperatures decrease metabolism and high temperatures may inactivate the lipase. Low initial moisture of the substrate hinders mass transfer and may cause the loss of functional properties of enzymes necessary to cell metabolism [20]. On the other hand, excess of water may reduce the substrate porosity hindering heat and mass transfer [4].…”
Section: Supplementation Effect On Lipase Activitymentioning
confidence: 99%